Improvement of application and enforcement of the sentence in the form of arrest by amending the criminal code of Ukraine - Автухов, К. А. (Problems of legality, 2013)
The basic problem of the Criminal Code of Ukraine (2001) in terms of the improvement of application and execution sentence of arrest. The new wording of Articles 391, 392, 393 of the criminal law. Discusses the need to amend the sanctions century. 395 of the Criminal Code of Ukraine to minimize assignment arrested persons criminal legal impact of this kind of punishment is unlikely.